Study of indoor air quality in school buildings in Argolida’s Sector at the Region of Peloponnese in Greece and potential Health Risks - Maria Anna Bikaki; Georgios Dounias; Olga Cavoura; Georgios Farantos; Ioanna Damikouka; Lefkothea Evrenoglou (European Scientific Journal, ESJ, 2024)
Aims and scope: Indoor air quality (IAQ) in schools is very important, as students spend more time in school environments besides home. Epidemiological researches have shown that indoor pollutants are associated with several health and respiratory problems. The aim of the present study was to investigate the indoor air quality (IAQ) in school buildings in the Argolida’s Sector at the Region of Peloponnese in Greece. Methods: The study was conducted in fourteen (14) classrooms in a total of seven (7) school buildings in the Argolida’s Sector at the Region of Peloponnese during March 2022 to May 2023. Physical parameters such as temperature (T) and relative humidity (RH) and air pollutants Carbon monoxide (CO), Carbon dioxide (CO2), Nitrogen dioxide (NO2), Volatile Organic Compounds (VOC’s), Particulate matters PM (PM10, PM2.5) were monitored by the series 500 Portable Air Quality Monitor AeroQual, during (1) teaching hour per day in each classroom. Due to governmental measures to protect public health against the risk of further spread of COVID-19, some windows and doors in the classrooms were opened during the samplings. Findings: Mean temperature and relative humidity inside the classrooms was 22,12 oC and 50,87% respectively. The overall mean concentrations of air pollutants recorded inside the schools were 691,35ppm CO2, 0,001ppm NO2, 9,97ppm VOC’S, 15,7μg/m3 PM10 and 11,4μg/m3 PM2.5. No indoor CO concentration (0 ppm) was detected in all classrooms. In this study: a) in all schools (100%) indoor concentration levels of CO2 were below 1000ppm, b) in five (5) of fourteen (14) classrooms (35,7%) in the school buildings were detected concentration levels of CO2 more than 700ppm. In all schools (100%) indoor concentration levels of VOC’s were more than 0,8ppm. Eight (8) classrooms (57,1%) in Argolida’s school buildings had no comfort conditions, due to the high levels of relative humidity (RH>50%). There was a statistically significant difference for temperature (p=0,001), CO2 (p<0,001), NO2 (p=0,006) and VOC’s (p=0,001) between indoor and ambient air. Conclusion: The air quality in school buildings in the Argolida’s Sector was affected by the number of students inside a classroom, the ventilation rate and school’s equipment. The location of schools near central roads and construction activities played role on the concentration of indoor air pollutants. Indoor air pollution (IAP) can lead to potential health risks. The development of monitoring systems for measuring indoor pollutants in schools as well as strategies for control and enhancement of IAQ are considered essential for Public Health.